Amphibious all terrain unmanned ground vehicle - Abdul Rahman Abd Malek (2016)
With the Earth surface being covered with about 71% of water, humans have been constantly finding ways to travel over water surfaces efficiently. And on the big part of that, there are constant research on building fully amphibious vehicles. Therefore, ultimately, the objective is to design and fabricate an amphibious vehicle that in the future will be able to house modules like sensors and robotic arms. With the ability to suit this vehicle to different operational needs, it will enable the vehicle to be used in different missions such as search and recovery missions. For this project itself, the main aim is to fabricate the base vehicle only.